Interactive digital media and impact of customer attitude and technology on brand awareness: evidence from the South Asian countries - Ahmed, Rizwan Raheem; Vveinhardt, Jolita; Streimikiene, Dalia (Journal of Business Economics and Management, 2017)
The purpose of this study is to investigate the role of interactive digital media channels such as social media, email marketing, and mobile marketing in creating the brand awareness. We have assimilated three behavioral factors including perceived value, trust, and word of mouth as mediating factors, and the Internet and smartphone as moderating variable. Total 2565 responses have been taken to investigate the role of digital media channels, and impact of mediating and moderating variables on the brand awareness. This research has used SEM-based multivariate approach including exploratory factor analysis, confirmatory factor analysis, and conditional process technique for examining the direct and indirect influence of variables. The results of the study exhibited that the interactive digital media channels have a positive and significant direct impact on brand awareness. Results further revealed that the perceived value, trust, and word of mouth as mediating factors, and the Internet and smartphone as moderating variables have a significant and influential impact in a relationship of interactive digital media tools and the brand awareness.